PENGARUH PERBANDINGAN EKSTRAK DAUN MATOA (Pomentia pinnata) DENGAN EKSTRAK DAUN SIRIH (Piper betle L.) DAN PENAMBAHAN MADU TERHADAP MUTU MINUMAN HERBAL - M., Rizkah Syarazani; Suhaidi, Ismed; Ginting, Sentosa (Journal of Food Technology and Agroindustry dipublikasikan oleh Universitas Wiraraja, 2024)
Herbal drink is a functional food that is well known for its taste, antidote to free radicals and health benefits. The purpose of this research is to use matoa leaves, betel leaves and honey with the best composition for herbal drinks with the best physical and chemical characteristics. This study used a factorial completely randomized design (CRD) with two factors, namely the ratio of matoa leaf extract (Pomentia pinnata) to betel leaf extract (Piper betle L.) (7:3, 5:5, 3:7) and the addition of honey (5 %, 10%, 15%). Parameters observed were total dissolved solids, degree of acidity (pH), color (oHue), total flavonoids, antioxidant activity, and organoleptic tests. The results of this study showed that the comparison of leaf extract with betel leaf extract yielded highly significant differences (P<0.01) to the flavonoid tatal, antioxidant activity and organoleptic taste and the addition of honey showed highly significant results (P<0.01) to total solids dissolved, pH, color (oHue), total flavonoids, antioxidant activity, organoleptic color and taste. The interaction effect of the ratio of matoa leaf extract with betel leaf extract and the addition of honey showed highly significant (P<0.01) results for total flavonoids, and significantly different (P<0.05) for antioxidant activity. The results of this study showed that the P1M3 treatment (the ratio of mato leaf extract to betel leaf was 7:3 and the addition of 15% honey) was the best treatment.